Bits and pieces: A survey characterizing equipment use on the heads of therapeutic/adaptive riding horses in the United States - Sarah Jean Reega; Sarah K. Matlock; Sharon Butler; Kathleen R. Auchmoody; Ann M. Hess; B. Caitlin Peters (Journal of Veterinary Behavior, 2026)

Ecological Benthic Units: A New Characterization of the Global Seafloor for Ocean Spatial Planning and Management - Peter Harris; Dawn Wright; Kevin Butler; Keith VanGraafeiland; Mark Costello; Kerry Howell; Gustav Kågesten; Vanessa Lucieer; Miles Macmillan-Lawler; Roger Sayre (Oceanography, 2026)
Effective management of deep-sea ecosystems and the high seas is hindered by the absence of a globally consistent framework for characterizing benthic habitats. Here we present the first global ecological classification of the seafloor, comprising 250 unique ecological benthic units (EBUs), distributed on the seafloor as nearly 700,000 EBU polygon occurrences, generated by intersecting a high-resolution geomorphic map with multivariate environmental seascapes. Using 17 million seafloor data points and 0.05° resolution biophysical datasets—including bottom temperature, dissolved oxygen, pH, carbon flux, sediment thickness, crustal age, and bottom currents—we identified 57 benthic regions across six major geomorphic groups (shelves, slopes, seamounts/guyots, spreading ridges, abyssal/hadal areas, plateaus). The resulting EBUs reveal previously unrecognized ecological gradients, quantify global patterns of benthic heterogeneity, and expose large-scale environmental vulnerabilities. Notably, we find that 95.6 million km2 (26% of the ocean area) of abyssal seafloor lies below the carbonate compensation depth, that 4.16 million km2 (1% of the ocean) of continental slopes intersect severe oxygen minima, and

Sequential model-based design of experiments for a heat-integrated biomass downdraft gasifier - Houda M. Haidar; James W. Butler; Peter Gogolek; Kimberley B. McAuley (Bioresource Technology, 2025)

Comparison of the air kerma standards of ARPANSA, Australia, and the IAEA in RQR, RQA, and RQT diagnostic X-ray beams - Kam L. Lee; Zakithi Msimang; Duncan Butler; Peter Thomas; Joao Cardoso (Physical and Engineering Sciences in Medicine, 2025)
A comparison of air kerma standards between the Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) and the International Atomic Energy Agency (IAEA) was carried out for the RQR, RQA and RQT radiation qualities (as prescribed by IEC 61267 or IAEA TRS 457) using two ionisation chambers as transfer standards. The ratios between the IAEA and ARPANSA calibration coefficients ranged between 0.993 and 0.997 for RQR beams, 0.990 and 0.999 for RQA beams, and 0.993 to 0.994 for RQT beams. The relative expanded uncertainty for IAEA and ARPANSA was 1.2 and 1.4% respectively, and the comparison results agree at around the level of, or better than, the combined standard uncertainty of 0.74% for all the beams.

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

Allometric aboveground biomass equations to quantify carbon content of Southeast Australian saltmarsh vegetation - Jami Butler; Clare Duncan; Paul E. Carnell; Anirban Akhand; Stacey M. Trevathan-Tackett; Peter I. Macreadie (Regional Studies in Marine Science, 2025)

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Generalized Stomatal Optimization of Evolutionary Fitness Proxies for Predicting Plant Gas Exchange Under Drought, Heatwaves, and Elevated CO 2 - Aaron Potkay; Antoine Cabon; Richard L. Peters; Patrick Fonti; Gerard Sapes; Anna Sala; Artur Stefanski; Ethan Butler; Raimundo Bermudez; Rebecca Montgomery; Peter B. Reich; Xue Feng (Global Change Biology, 2025)
Stomata control plant water loss and photosynthetic carbon gain. Developing more generalized and accurate stomatal models is essential for earth system models and predicting responses under novel environmental conditions associated with global change. Plant optimality theories offer one promising approach, but most such theories assume that stomatal conductance maximizes photosynthetic net carbon assimilation subject to some cost or constraint of water. We move beyond this approach by developing a new, generalized optimality theory of stomatal conductance, optimizing any non‐foliar proxy that requires water and carbon reserves, like growth, survival, and reproduction. We overcome two prior limitations. First, we reconcile the computational efficiency of instantaneous optimization with a more biologically meaningful dynamic feedback optimization over plant lifespans. Second, we incorporate non‐steady‐state physics in the optimization to account for the temporal changes in the water, carbon, and energy storage within a plant and its environment that occur over the timescales that stomata act, contrary to previous theories. Our optimal stomatal conductance compares well to observations from seedlings, saplings, and mature trees from field and greenhouse experiments. Our model predicts predispositions to mortality during the 2018 European drought and captures realistic responses to environmental cues, including the partial alleviation of heat stress by evaporative cooling and the negative effect of accumulating foliar soluble carbohydrates, promoting closure under elevated CO 2 . We advance stomatal optimality theory by incorporating generalized evolutionary fitness proxies and enhance its utility without compromising its realism, offering promise for future models to more realistically and accurately predict global carbon and water fluxes.

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Modeling of a heat-integrated biomass downdraft gasifier: Influence of feed moisture and air flow - Houda M. Haidar; James W. Butler; Samira Lotfi; Anh-Duong Dieu Vo; Peter Gogolek; Kimberley McAuley (Biomass and Bioenergy, 2024)

Pleistocene shifts in Great Basin hydroclimate seasonality govern the formation of lithium-rich paleolake deposits - Tripti Bhattacharya; Peter R. Brennan; Daniel E. Ibarra; Catherine A. Gagnon; Kristina L. Butler; Alexa Terrazas; Shaw Miller; Lee Ann Munk; David F. Boutt; Ran Feng; Stephanie N. Bullinger; Lucy Weisbeck (Quaternary Science Reviews, 2024)

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Assessing Public Preferences of Landscape and Landscape Attributes: a Case Study of the Proposed Appalachian Geopark Project in West Virginia, USA - Ganga Nakarmi; Michael P. Strager; Charles Yuill; Jasmine C. Moreira; Robert C. Burns; Peter Butler (Geoheritage, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Landscape Characterization and Assessment of a Proposed Appalachian Geopark Project in West Virginia, United States - Ganga Nakarmi; Michael P. Strager; Charles Yuill; Jasmine C. Moreira; Robert C. Burns; Peter Butler (Geoheritage, 2023)

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wildlife conservation in a fragmented landscape: the Eurasian red squirrel on the Isle of Wight - Emilie A. Hardouin; Helen Butler; Marin Cvitanović; Rainer G. Ulrich; Vanessa Schulze; Anna-Katarina Schilling; Peter W. W. Lurz; Anna Meredith; Kathy H. Hodder (Conservation Genetics, 2021)
Island populations may have a higher extinction risk due to reduced genetic diversity and need to be managed effectively in order to reduce the risk of biodiversity loss. The Eurasian red squirrels ( Sciurus vulgaris ) in the south of England only survive on three islands (the Isle of Wight, Brownsea and Furzey islands), with the Isle of Wight harbouring the largest population in the region. Fourteen microsatellites were used to determine the genetic structure of red squirrel populations on the Isle of Wight, as well as their relatedness to other populations of the species. Our results demonstrated that squirrels on these islands were less genetically diverse than those in Continental mainland populations, as would be expected. It also confirmed previous results from mitochondrial DNA which indicated that the squirrels on the Isle of Wight were relatively closely related to Brownsea island squirrels in the south of England. Importantly, our findings showed that genetic mixing between squirrels in the east and west of the Isle of Wight was very limited. Given the potential deleterious effects of small population size on genetic health, landscape management to encourage dispersal of squirrels between these populations should be a priority.

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

A Global Ecological Classification of Coastal Segment Units to Complement Marine Biodiversity Observation Network Assessments - Roger Sayre; Kevin Butler; Keith Van Graafeiland; Sean Breyer; Dawn Wright; Charlie Frye; Deniz Karagulle; Madeline Martin; Jill Cress; Tom Allen; Rebecca Allee; Rost Parsons; et al. (Oceanography, 2021)
A new data layer provides Coastal and Marine Ecological Classification Standard (CMECS) labels for global coastal segments at 1 km or shorter resolution. These characteristics are summarized for six US Marine Biodiversity Observation Network (MBON) sites and one MBON Pole to Pole of the Americas site in Argentina. The global coastlines CMECS classifications were produced from a partitioning of a 30 m Landsat-derived shoreline vector that was segmented into 4 million 1 km or shorter segments. Each segment was attributed with values from 10 variables that represent the ecological settings in which the coastline occurs, including properties of the adjacent water, adjacent land, and coastline itself. The 4 million segments were classified into 81,000 coastal segment units (CSUs) as unique combinations of variable classes. We summarize the process to develop the CSUs and derive summary descriptions for the seven MBON case study sites. We discuss the intended application of the new CSU data for research and management in coastal areas.

Enhanced light interception and light use efficiency explain overyielding in young tree communities - Laura J. Williams; Ethan E. Butler; Jeannine Cavender‐Bares; Artur Stefanski; Karen E. Rice; Christian Messier; Alain Paquette; Peter B. Reich (Ecology Letters, 2021)
Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here we investigated whether light interception alone or in combination with light use efficiency (LUE) of dominant and subordinate species explained greater productivity of mixtures relative to monocultures (i.e. overyielding) in 108 young experimental tree communities. We found mixed‐species communities that intercepted more light than their corresponding monocultures had 84% probability of overyielding. Enhanced LUE, which arose via several pathways, also mattered: the probability of overyielding was 71% when, in a mixture, species with higher ‘inherent’ LUE (i.e. LUE in monoculture) intercepted more light than species with lower LUE; 94% when dominant species increased their LUE in mixture; and 79% when subordinate species increased their LUE. Our results suggest that greater light interception and greater LUE, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests.

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Lack of alarm calls in a gregarious bird: models and videos of predators prompt alarm responses but no alarm calls by zebra finches - Nicole E. Butler; Robert D. Magrath; Richard A. Peters (Behavioral Ecology and Sociobiology, 2017)

A Three-Dimensional Mapping of the Ocean Based on Environmental Data - Roger Sayre; Dawn Wright; Sean Breyer; Kevin Butler; Keith Van Graafeiland; Mark Costello; Peter Harris; Kathleen Goodin; John Guinotte; Zeenatul Basher; Maria Kavanaugh; Patrick Halpin; et al. (Oceanography, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Fire, soil fertility and delayed seed release: a community analysis of the degree of serotiny - Peter J. Clarke; Kirsten E. J. Knox; Damian Butler (Evolutionary Ecology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Metal Accumulation From Dietary Exposure in the Sea Urchin, Strongylocentrotus droebachiensis - Gretchen K. Bielmyer; Tayler A. Jarvis; Benjamin T. Harper; Brittany Butler; Lawrence Rice; Siobhan Ryan; Peter McLoughlin (Archives of Environmental Contamination and Toxicology, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

An in vivo model of melanoma: treatment with ATP - Nicholas White; Gillian E. Knight; Peter E. M. Butler; Geoffrey Burnstock (Purinergic Signalling, 2009)

A highly selective, orally bioavailable, vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor has potent activity in vitro and in vivo - Kenneth R. LaMontagne; Jeannene Butler; Virna B. Borowski; Angel R. Fuentes-Pesquera; Jonathan M. Blevitt; Shenlin Huang; Ronghua Li; Peter J. Connolly; Lee M. Greenberger (Angiogenesis, 2009)

Mammalian browsing impact on regenerating Eucalyptus seedlings in a large commercially managed native forest estate - Julian Di Stefano; Kym Butler; Ian Sebire; Peter Fagg (New Forests, 2009)

Relationship between pancreatic vesicular monoamine transporter 2 (VMAT2) and insulin expression in human pancreas - Yoshifumi Saisho; Paul E. Harris; Alexandra E. Butler; Ryan Galasso; Tatyana Gurlo; Robert A. Rizza; Peter C. Butler (Journal of Molecular Histology, 2008)

Many Commercially Available Antibodies for Detection of CHOP Expression as a Marker of Endoplasmic Reticulum Stress Fail Specificity Evaluation - Leena Haataja; Tatyana Gurlo; Chang-jiang Huang; Peter C. Butler (Cell Biochemistry and Biophysics, 2008)

A note on the top-down and bottom-up gradient functions over a forested site - Weiguo Wang; Kenneth J. Davis; Chuixiang Yi; Edward G. Patton; Martha P. Butler; Daniel M. Ricciuto; Peter S. Bakwin (Boundary-Layer Meteorology, 2007)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Human melanomas express functional P2X7 receptors - Nicholas White; Peter E. M. Butler; Geoffrey Burnstock (Cell and Tissue Research, 2005)

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)